Widely tunable (2.6–10.4 μm) BaGa4Se7 optical parametric oscillator pumped by a Q-switched Nd:YLiF4 laser. (22nd March 2018) - Kolker, D B; Kostyukova, N Yu; Boyko, A A; Badikov, V V; Badikov, D V; Shadrintseva, A G; Tretyakova, N N; Zenov, K G; Karapuzikov, A A; Zondy, J-J
Abstract: We report on the first BaGa4 Se7 nanosecond optical parametric oscillator pumped by Q-switched Nd:YLiF4 laser at 1053 nm. The oscillator exhibits a pump threshold energy as low as 0.25 mJ. Mid-infrared (MIR) idler wave tuning from 2.6 μ m to 10.4 μ m is demonstrated with an angle-tuned type-I ( o-ee ) y -cut sample, highlighting the superior performance of this novel large bandgap chalcogenide nonlinear crystal to generate tunable coherent radiation over its full MIR transparency range (0.47–18 μ m). The phase-matching data are used to identify the most accurate dispersion relations of this compound among three recently published Sellmeier equations. Damage threshold measurements yielded values as high as 2.04 J cm −2 at 100 Hz pulse repetition rate, one of the largest among existing MIR χ (2) nonlinear materials.